Larva and pupa of Nilio (Linio) lanatus Germar, 1824 (Coleoptera: Tenebrionidae) - Simões, Marianna V. P.; Quintino, Hingrid Y. S.; Monné, Marcela L. (Zootaxa, 2009)
The larva and pupa of Nilio (Linio) lanatus Germar, 1824 are described and illustrated. The larva of Nilio (L.) lanatus differs from the other known larvae of the genus mainly by the body elongate covered with black and white hairs, the head with four stemmata and the mesothorax with one pair of ventral annular spiracles. Biological observations were made in Atlantic Forest, in the Parque Nacional do Itatiaia, Rio de Janeiro (Brazil).